When is my birthday? - Sipherd, Ray.; Cooke, Tom.; Children's Television Workshop ([New York] : A Sesame Street/Golden Press Book, 1988)
Little Elmo helps Mom prepare a birthday party for big sister Daisy.
"Featuring Jim Henson's Sesame Street Muppets."
"A Sesame Street/Golden Press book."
"A Golden book"--Cover.
Keywords: Birthdays -- Fiction; Parties -- Fiction; Puppets -- Fiction